The Influence of Interpersonal Competence and Organizational Climate on Employee Performance with Motivation as an Intervening Variable at UPT PLN Malang - Didik Priyo Sugiharto Didik; Marli Marli (LP2M IAIN Palopo, 2026)
This study aims to analyze the influence of interpersonal competence and organizational climate on employee performance with motivation as an intervening variable at UPT PLN Malang. The method used is a quantitative approach with an explanatory design, and uses Partial Least Squares Structural Equation Modeling (PLS-SEM) to test the relationship between variables. The results of the study indicate that interpersonal competence and organizational climate have a positive and significant influence on employee motivation. Furthermore, motivation is proven to play a role as an intervening variable that strengthens the relationship between interpersonal competence and organizational climate with employee performance. These findings emphasize the importance of developing interpersonal competence and creating a conducive organizational climate to increase motivation, which ultimately has a positive impact on improving employee performance at UPT PLN Malang.